Perspectives on palliative and end-of-life care disease, social and cultural context - Allen, Rebecca S. (Aging and mental health research, 2018)
(USA)Chapter Seven: Policy and practice on psychosocial care in palliative care programs Chapter by Guldin and Payne (Europe)Scope of the Book IIWith perspectives from experienced clinicians, providers, and caregivers from around the world, the book offers a strong foundation in contemporary evidence-based practice alongside seasoned practice insights from the field and explores interventions for people as diverse as HIV caregivers in Africa and individuals dying with dementia. In addition, readers will learn about the process of caring for individuals with chronic illnesses including severe mental illness; weigh the impact of policy regulations on the availability of and access to palliative care and interventions; and be able to compare the different issues experienced by family caregivers and formal caregivers